Racism towards Roma in the Czech Republic - Prasilova, Petra (KDI School, 2011)
The Czech Republic and its citizens have been perceived as a tolerant and liberty loving nation since the Velvet Revolution in 1989. Despite strong values, a problem has appeared and risen into the scale that divides the country into two camps ? the Romani minority and the dominant society. Racism, xenophobia and hatred became words used in media more often than would be suitable for a broadminded and liberal country with strong values. The government has not managed to solve or even improve this striking issue, and therefore the civil society has taken its turn to bring the two worlds back together, and improve the position of Roma as a self-confident, self-aware ethnicity with its own language, culture, customs and opportunity to maintain them, develop and transmit to next generations as well as share them with the dominant society. The thesis intends to show whether the civil society grew strong enough to manage its role and what it needs to focus on. Furthermore, it indicates the responsibility and position of the Czech government in this problem and the relationship between the government and the civil society.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Czech Republic